Label Noise Correction via Fuzzy Learning Machine - Liang, Jiye; Li, Yixiao; Cui, Junbiao (Proceedings of the AAAI Conference on Artificial Intelligence, 2025)
The ubiquitous and unavoidable label noise brings great challenges to the generalization performance of learning methods.Label noise correction aims to detect and correct label noise in the data, which is one of the most potential methods to address this challenge.Current methods for label noise filtering that utilize primitive features primarily concentrate on identifying noise, which often limits their capacity to adaptively learn features crucial for specific tasks, thereby resulting in a higher rate of noise identification within the noise recognition process. On the other hand, deep neural networks, endowed with robust feature extraction capabilities, typically exhibit lower noise identification, as they are prone to fitting noise patterns during the recognition process, potentially undermining their overall efficacy. Moreover, Fuzzy Learning Machine (FLM) excels not only in feature extraction but also in noise tolerance, adeptly navigating data uncertainties. FLM enhances the accuracy of the labels by calculating the membership degrees of samples across categories and determining their fuzzy memberships. The introduction of a two-stage FLM-based framework, which employs a secondary learning mechanism for precise noise filtering and correction, has shown substantial improvements in noise correction across various large-scale noisy datasets, thereby significantly enhancing samples' quality and boosting the generalization capabilities of classifiers.